Cervical vestibular evoked myogenic potentials via air conduction delivered by either sequentially or quasi-simultaneously presented narrow-band chirp stimuli. (4th March 2019) - Cebulla, Mario; Walther, Leif Erik
Abstract: Objective: To produce sound-evoked cervical vestibular evoked myogenic potentials (cVEMPs). These are widely used for the diagnosis of peripheral vestibulopathies and disturbances of the sacculocollic reflexes. The main, sensitive, frequency for eliciting cVEMPs has been shown to be around 500 Hz. Design: Narrow-band chirps in different frequency ranges (middle frequencies of 0.5, 1, 2 and 4 kHz) will be used for sequential and quasi-simultaneous stimulation of the cervical vestibular organ. As benchmarks, peak-to-peak p13 and n23 amplitudes were analysed. Study samples: The pilot study used five normal-hearing subjects (mean age 38.6 years) none of whom have balance disorders. Results: From 40 measurements, p13 and n23 could be identified in a total of 34 detected cVEMPs. As expected, amplitudes were highest at 500 Hz, followed by 1, 2 and 4 kHz. Using the quasi-simultaneous stimulation method led to a slight reduction in cVEMP amplitudes, but these remained in the same order according to magnitude: 0.5, 1, 2 and 4 kHz. Conclusion: Sequential and quasi-simultaneous narrow-band chirps are effective for evoking cVEMPs. High amplitudes contribute to fast identification across an extended frequency range (0.5–4 kHz) and also contribute to a reduction in examination time and overall sound exposure.